2021
DOI: 10.24940/theijbm/2021/v9/i2/bm2102-011
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Role of Perceived Transparency on the Relationship between Service Fairness and Customer Loyalty

Abstract: In recent times, the marketing literature has seen increase interest in customer loyalty. Organizations around the globe struggle to acquire and retain their customers. The concept has no doubt continued to gain prominence among marketing researchers. Although the literature suggests that there is no single universally acceptable definition of the construct (Gaurav, 2016), Oliver (1999) viewed it as an intense commitment to re-buy or re-patronize a product or service of choice over a long period of time. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Numerous studies in the literature suggest that a customer's level of personal loyalty to a service provider has a positive effect on the customer's citizenship behavior (Abdulaziz & Maiyaki, 2018;Anaza & Zhao, 2013;Bove et al, 2009;Hu, Huang, Yan, Liu, & Zhang, 2020;Tung et al, 2017;Van, Chi, Chi, & Quang, 2016). Bartikowski and Walsh (2011) concluded that customer loyalty affects the customer's helping behavior but has no effect on helping other customers.…”
Section: Customer Loyalty and Customer Citizenship Behaviormentioning
confidence: 99%
“…Numerous studies in the literature suggest that a customer's level of personal loyalty to a service provider has a positive effect on the customer's citizenship behavior (Abdulaziz & Maiyaki, 2018;Anaza & Zhao, 2013;Bove et al, 2009;Hu, Huang, Yan, Liu, & Zhang, 2020;Tung et al, 2017;Van, Chi, Chi, & Quang, 2016). Bartikowski and Walsh (2011) concluded that customer loyalty affects the customer's helping behavior but has no effect on helping other customers.…”
Section: Customer Loyalty and Customer Citizenship Behaviormentioning
confidence: 99%